A framework for conceptualising the organisational communications of a project management office. (23rd April 2021) - Ershadi, Mahmoud; Jefferies, Marcus; Davis, Peter; Mojtahedi, Mohammad
The project management office (PMO) plays a key role in linking the strategic and operational levels of a project-based enterprise. Fulfilling this mission requires effective collaboration with stakeholders since PMOs can no longer operate in organisational silos. This research aims to tackle the knowledge gap regarding the conceptualisation of the content of PMO communications in project-based organisations. A critical literature review and qualitative synthesis were conducted to draw conclusions concerning the existing theoretical discussions on the topic. The results are presented in the form of a framework explaining 11 categories of stakeholders and respective potential communications with them in four directions: horizontal, vertical upward, vertical downward and external. This study extends the literature by introducing a new theoretical framework of PMO communications and providing an insight into the main constituents required for maintaining effective relationships with stakeholders in practice.